2021
DOI: 10.1016/j.jse.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for symptomatic retears after arthroscopic repair of full-thickness rotator cuff tears

Abstract: Background: Factors affecting a rotator cuff symptomatic retear after arthroscopic repair have yet to be clearly identified, since they usually influence the surgical decisions. Methods: Consecutive patients with full-thickness tear of the supraspinatus who underwent arthroscopic repair were retrospectively analyzed. Cases of symptomatic retear, defined as Sugaya type IV and V on magnetic resonance imaging, associated with intensive pain and/or functional impairment were identified at follow-up. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
25
1
Order By: Relevance
“…In order to determine which patients may be good candidates for biological augmentation during RCrepairs, it is important to understand how patient demographics alter characteristics of CTPs, as this may affect healing. Patients who are old, obese, diabetic, and smoke have previously been reported to have higher rates of RC repair failures compared to healthy patients [32][33][34][35]. Muench et al was the first to demonstrate that SB CTPs demonstrated high proliferation potential regardless of patient demographics and RC tear characteristics [36].…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine which patients may be good candidates for biological augmentation during RCrepairs, it is important to understand how patient demographics alter characteristics of CTPs, as this may affect healing. Patients who are old, obese, diabetic, and smoke have previously been reported to have higher rates of RC repair failures compared to healthy patients [32][33][34][35]. Muench et al was the first to demonstrate that SB CTPs demonstrated high proliferation potential regardless of patient demographics and RC tear characteristics [36].…”
Section: Introductionmentioning
confidence: 99%
“…After further reading the full text, according to the inclusion and exclusion criteria established in this study, 14 documents were finally included. 10,15,18,28,30,33,[35][36][37]39,40,44,46,53 The specific retrieval process and results are shown in Fig. 1.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Only 1 article 18 had an NOS score of 6, and the average NOS score was 7.7 points, which indicates that the quality of the included literature was very high. The literature quality evaluation details of the 14 included studies 10,15,18,28,30,33,[35][36][37]39,40,44,46,53 are shown in Supplementary Material S3.…”
Section: Literature Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of risk factors reported in meta-analyses of outcomes of rotator cuff surgery that can contribute to a higher rate of re-tearing. These include age [ 55 ], size of the initial tear [ 56 ], level of post-surgical activity [ 57 ], prior corticosteroid administration [ 58 ], low HDL levels [ 59 ] as well as co-existent shoulder pathology or a fibro-inflammatory genotype of the repaired tendon [ 60 ] and further studies will be required to determine the causes of re-tearing following augmentation of RC repairs with BCS.…”
Section: Discussionmentioning
confidence: 99%